Avaliação de implantes ósseos de titânio e hidroxiapatita com revestimento biomimético - Medeiros, Waléria Silva de (2009)
Nowadays, there are several biomaterials used in Medicine and Dentistry which are able to rehabilitate patients and improve their quality of life. The purpose of this study was to produce a biomimetic coating onto porous titanium (Ti) and hydroxyapatite (HA) granulates, evaluate the physico-chemical and biological coating properties. In addition, it was aimed to produce a three-dimensional porous Ti scaffold by powder technique, stoichiometric HA granulates, analyze the biomaterials by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), scanning electron microscope (SEM) and energy dispersive X-ray (EDX); evaluate the bone repair in the presence of HA granulates coated by simplified body fluid solution (sFCS), especially the type of inflammatory response and giants cells. HA (granulates and disks) were characterized to verify the differences between results. HA samples (granulates and disks) were immersed in sFCS solution for 3h, 1, 3, 7, 14 e 28 days. Porous Ti was soaked in sFCS for 3h, 1 e 3 days. HA soaked for 14 days was used in dental socket of Rattus norvegicus (Wistar). Physico-chemical analyses of porous Ti have shown the deposition of calcium phosphate coating after 3h in sFCS. FTIR analysis showed 1190 cm-1 , 1184 cm-1 and 929 cm-1 peaks which suggest the presence of octacalcium phosphate (OCP). SEM and EDX of HA granulates did not identify the biomimetic coating (calcium phosphate crystals). HA disks for 14 days in solution presents a uniform biomimetic film similar to the morphology identified on HA (28 days). Physico and chemically analyzes have shown a film deposition. XRD analysis of HA disks did not show the biomimetic film deposition. Histological analyses have shown that HA coated had better bone repair than those HA without biomimetic coating (control group). A FCS solution was capable to coat both porous Ti and HA. Coated HA in vivo has shown a great potential of bone repair